The Importance of Keto-Enol Forms of Arylpropanoids Acting as Antifungal Compounds - S. Zacchino; R. Furlan; H. Baldoni; F. Suvire; R. Enriz; A. RodrÃƒÂguez; C. Devia; F. Giannini (Molecules, 2000)
We report here the importance of a keto-enol equilibrium of an arylpropanoid series acting as antifungal agents. An interesting relationship between ln MIC, ∆E enolization and net atomic charges was found. Two compounds were synthesized and their MIC evaluated in order to prove the above relationship.